Plant-based diet and risk of all-cause mortality: a systematic review and meta-analysis - Tan, Junwen; Zhang, Shipeng; Jiang, Yanjie; Li, Jie; Yang, Chuan (Frontiers in Nutrition, 2024)
Abstract Objective: A systematic analysis was conducted to determine the relationship between a plant-based diet and all-cause mortality. Methods: The PubMed, Embase and Web of Science databases were searched. Two authors selected English documents from the database. Then the other two authors extracted the data and evaluated the Newcastle‒Ottawa Scale (NOS). This study adhered to the guidelines of the Preferred Reporting Project (PRISMA) and the PROSPERO Registry protocols. A mixed–effects model combined maximum adjusted estimates, with heterogeneity measured using the I2 statistic. The sensitivity analysis validated the analysis’s robustness, while publication bias was assessed. Results: The results of the meta-analysis of 14 articles revealed that a plant-based diet (PDI) can reduce cancer mortality (RR=0. 88, [95% CI 0. 79-0. 98], τ2: 0. 02, I2: 84. 71%), cardiovascular disease (CVD) mortality (RR=0. 81, [95% CI 0. 76-0. 86], τ2: 0. 00, I2: 49. 25%) and mortality (RR=0. 84, [95% CI 0. 79-0. 89], τ2: 0. 01, I2: 81. 99%) risk. Adherence to a healthy plant-based diet (hPDI) was negatively correlated with cancer mortality (RR=0. 91, [95% CI 0. 83-0. 99], τ2:0. 01, I2:85. 61%), CVD mortality (RR=0. 85, [95% CI 0. 77-0. 94], τ2: 0. 02, I2: 85. 13%) and mortality (RR=0. 85, [95% CI 0. 80-0. 90], τ2: 0. 01, I2: 89. 83%). An unhealthy plant-based diet (uPDI) was positively correlated with CVD mortality (RR=1. 19, [95% CI 1. 07-1. 32], τ2: 0. 02, I2: 80. 03%) and mortality (RR=1. 18, [95% CI 1. 09-1. 27], τ2: 0. 01, I2: 89. 97%) and had a certain correlation with cancer mortality (RR=1. 10, [95% CI 0. 97-1. 26], τ2: 0. 03, I2: 93. 11%). Sensitivity analysis showed no contradictory results. Conclusions: The hPDI was negatively associated with all-cause mortality, and the uPDI was positively associated with all-cause mortality.